KN-62 provides neuroprotection against glutamate-induced excitotoxicity in neurons. - Gao Can; Zhang Guang-yi (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of KN-62, an inhibitor of Ca(2+)-calmodulin dependent protein kinase II (CCDPK II), on the damage of cortical neurons and mechanisms of the loss of CCDPK II activity induced by sodium glutamate (Glu). METHODS: CCDPK II activity was measured by 32P incorporation and backphosphorylations of endogenous proteins were studied by autoradiography. RESULTS: 1) KN-62 provided partial protection against excitotoxical damage only before Glu (100 mumol.L-1, 10 min) treatment. 2) KN-62 markedly suppressed the loss of CCDPK II activity induced by Glu from 48.0% to 90.6%. 3) Backphosphorylation of endogenous proteins (especially the 50 kDa protein) reduced to 78.2% of control after treatment with Glu, and the reduction was protected with KN-62 added before Glu. CONCLUSION: KN-62 provided the protection against excitotoxicity and the loss of CCDPK II activity as well as backphosphorylation of endogenous proteins induced by Glu. The neuroprotection provided by KN-62 was due to the inhibition of autophosphorylation of CCDPK II.